A robot or a dumper truck? Facilitating play-based social learning across neurotypes. (March 2022) - Paldam, Ella; Roepstorff, Andreas; Steensgaard, Rikke; Lundsgaard, Stine Strøm; Steensig, Jakob; Gebauer, Line
Structured abstract Background & aims: How can non-autistic adults facilitate social learning with children on the spectrum? A new theoretical understanding of autism is currently emerging that has made this question more relevant than ever. At the intersection of two growing research areas in the field of autism, the borderland that separates the experience of social interaction between neurotypes is increasingly mapped out. By integrating anthropological research on autistic sociality and the neurocognitive framework of predictive processing, this paper explores the question: If autistic people experience the world in a fundamentally different way, what is a meaningful strategy for supporting them in developing their socialities? Methods: The paper reports an in-depth analysis of a 2-min sequence in which a non-autistic adult facilitates a collaboration game between three autistic children (8–12 years). The data comes from a participatory research project that develops a new pedagogical approach to social learning based on open-ended construction play. The analytical strategy is informed by conversation analysis. Results: We find that the facilitation supports the children in accomplishing social interaction and collaboration, but it also in several instances gives rise to misunderstandings between the children. Whereas the facilitator aims to support the children's direct verbal communication about the construction task, we observe that the children use a broad repertoire of non-direct communication strategies that enables them to coordinate and align their shared process. We find that the children's actions with their hands in the construction task count as turns in the communication. Regarding the play-based learning environment, we find that the children are engaged in the shared construction task and that they competently navigate social tension when it arises without the facilitator's help. Conclusion: We conclude that the misunderstandings between the children created by the facilitation from a non-autistic adult emerge from a discrepancy of attention in the situation. The facilitator focuses on the words, but the children focus on the task. Even though this discrepancy is not necessarily a result of different neurotypes, we find that it emerges from the social dynamics of facilitation by non-autistic adults that is key in many social intervention settings. Furthermore, we conclude that the play-based learning environment enables the facilitator to support the children without directly instructing them in their social behavior. This appears to give the children an opportunity to acquire complex social experiences through their collaboration. Implications: The interaction dynamics in the data clip is shaped by the non-autistic adult's expectations of the children's interaction. This made us wonder whether we can establish a learning environment that begins from the learners' perspectives instead. The analysis caused us to change the facilitation strategy that we employ in our project. It is our hope that our approach will inspire reflection and curiosity in researchers and practitioners who develop social interventions targeting autistic people.